THE AUDIT OF CASHIER INFORMATION SYSTEMS IN PT. FOOD BEVERAGES INDONESIA (THE BRANCH OF CHATIME, BANTEN) USING COBIT 5.0 - Rohman, Itqu; Auliana, Sigit; Permana, Basuki Rakhim Setya (International Journal of Multidisciplinary Research and Literature, 2024)
This research focuses on the audit of the cashier information system at PT. Foods Beverages Indonesia (Serang Banten Branch), known as the Chatime brand. The background of this research is the importance of an effective and efficient cashier system in the digital era, especially for a leading beverage company like Chatime. The main objective of the research is to analyze how Chatime's current cashier information system works and evaluate the results using the COBIT 5 framework. The research method used is an information system audit using the COBIT 5 (Control Objectives for Information and Related Technologies) framework. This framework was chosen because it provides a collection of principles, practices, and frameworks that help companies achieve business goals through effective management of information technology. The results show several areas that require improvement, including the need for a clear classification scheme for managing service requests, strategic planning to address employee shortages, periodic evaluation of asset performance, and implementation of Total Cost of Ownership (TCO) analysis. The research conclusion emphasizes the importance of improvements in the management of Chatime's cashier information system, including better documentation, strategic human resource planning, regular performance evaluation, and implementation of comprehensive cost analysis. The recommendations resulting from this audit are expected to improve the efficiency and effectiveness of the cashier information system at Chatime Serang Banten Branch